FILM SANG PENARI : Sebuah Kajian Estetika Baumgarten - Afrianto, Damar Tri (Seni Media Rekam ISI Surakarta, 2016)
Film Sang Penari (The Dancer) is one of Indonesian film that has a local spirit.Ifa Ifansyah, director of this film presents the problematic female dancers Ronggeng, ranging from the problem itself with her culture,herself with her family,to herself with her love story. The film seems to provide another offer to bring local wisdom in the movie screen.This research uses ethical approach by applying interpretation of analysis with Baumgarten aesthetic theory.The presentation is presented in qualitative descriptive. Based on the aesthetic analysis are generated various perceptions of beauty as follows: 1) The filmSang Penari (The Dancer) has a unique plot power, the cornerstone of this plot is a flashback but only a small percentage. Then forwarded with a forward flow that dominates the plot in its entirely.2)The aesthetics in this film appear when presenting a complex suspense and surprises. Both aspects are beyond the expectations of the audience thought and blanket the mind of the audience. 3) The aesthetics revealed is how the power of displaying beauty-beauty through political symbols. 4) The next aesthetic that is revealed is the cultural aesthetic.The aesthetics of Ronggeng performing arts along with the aspects in them are clearly revealed in this film.Aesthetics displayed by a dancer Ronggeng not only on the beautiful and sensual movement, but also a Ronggeng is a representation of beauty in maintaining the agrarian society.Keywords:Film,Sang Penari,estetika,Ronggeng,dan Buamgarten